Microbial Relationship of Carious Deciduous Molars and Adjacent First Permanent Molars - Weihua Shi; Jing Tian; He Xu; Man Qin (Microorganisms, 2023)
(1) Epidemiological studies have shown that deciduous molar caries are related to and more severe than permanent molar caries. This study aimed to investigate whether caries subtypes in deciduous molars were associated with caries in first permanent molars and to explore taxonomic and functional profiles of the microbiota involved in different subtypes. (2) 42 mixed-dentition children were recruited and were divided into DMC (carious deciduous molars but caries-free first permanent molars; n = 14), C (carious deciduous and first permanent molars; n = 13), and control (n = 15) groups. Metagenomic sequencing was performed for supragingival plaque samples obtained separately from deciduous and first permanent molars. (3) The microbiota of deciduous molars in the DMC and C groups differed not only in species-based beta diversity but also in compositional and functional profiles. In the C group-like subtype, 14 caries-related species and potential pathways were identified that could be responsible for the caries relationship between the deciduous and permanent molars. In the DMC group-like subtype, the overall functional structure, the levels of Leptotrichia wadei, Streptococcus anginosus, and Stomatobaculum longum and KOs in sugar transporters and fermentation, quorum sensing, and TCA cycle in their first permanent molars surprisingly resembled those of the C group rather than the control group. This suggested that these clinically sound first permanent molars were at a greater risk for caries. (4) Classification of deciduous molar caries according to the microbiota could serve as a caries risk predictor for adjacent first permanent molars.